Teacher’s Strategies in Encouraging Students’ Participation in Speaking - Khairul Bariah (Universitas Syiah Kuala, 2017)
This study aims to know the teachers’ strategies in encouraging students’ participation by the English teacher in teaching speaking at SMA Labschool Unsyiah. In this study, the researcher collects data by conducting the observation the strategiesused by the English teacher regarding the learning process that is proposed by Gagne and Briggs (as cited in Yamin, 1997). From the result of classroom observation, it shows that the teacher has the same strategies that encourage the students to participate in teaching and learning process of the class. It is based on the theory stated by Gagne and Briggs namely motivating students to attractthe students’ attention, giving stimulus, giving the guidance of how to learn appropriately for students in conducting activities, encouraging students’ participation in learning process, doing some tests, creating opportunities for practice in using language inside or outside the classroom, and concluding each material that has been taught at the end of learning activity. Meanwhile, the result of interview reveals that the teacher tries to modify some strategies by doing a simple game to attract the students in the class.